A novel method for T2 quantification in presence of B1 inhomogeneities - Milford, David; Bendszus, Martin; Heiland, Sabine (Zeitschrift für medizinische Physik, 2012)
Introduction T3 relaxometry as a quantitative MRI technique offers a more precise characterization of tissue, compared with qualitative T2 weighted imaging. The issue, however, is that in typically used T2 relaxometry sequences such as a multi-spin echo sequences, incorrect refocussing flip angles and B1 inhomogeneities cause inaccuracies in T2 determination. The work presented here within presents a new technique for modelling T2 decay curves and thereby correcting T2 times altered by inhomogeneities. Materials and methods: The proposed technique models the signal decay acquired by multi-spin echo sequences based on extended phase graph theory. We have then put this new correction technique to test under both noise free and noise affected simulated signal and compared it to other previously introduced correction methods. To compare the efficacy of the T2 correction techniques, it was applied to MRI data acquired at 9.4Tesla. Results and conclusion: The results show that the proposed technique is able to minimize the systematic error in T2 relaxometry for a wide range of T2 times. Beyond that, the technique reveals the actual refocussing pulse angle in the respective voxel and reduces the error in So, which is mandatory if one aims for quantification of proton density.